The Preliminary Study of Utilizing Potato Peel Waste as a Sustainable Material in Adsorption of Oils (International Journal of Food and Nutritional Sciences, 2022)
Oil pollution management is one of the serious emerging environmental issue all over the world. Due to its biodegradation and buoyancy adsorption is considered as one of the cost effective technology for pollutant management. The use of eco-friendly and low cost adsorbent has been studied as an ideal alternative substitution to the current expensive methods for removal of oils. Potato peel, the most appropriate domestic and food processing industrial waste, is currently obtaining sufficient attraction, owning to its wide availability and potentiality in environmental conservation. The untreated potato peels were cut into small pieces and dried under sunlight for 48 hours. Then, it was further dried in an oven for 24 hours and ground into powder. The adsorbent was used to adsorb different types of oils such as diesel oil, used engine oil, and waste cooking oil with different amounts of adsorbent which is 0.1 g, 0.2 g, 0.3 g, 0.4g, and 0.5 g for adsorbent dosage experiment. This preliminary study aimed to use potato peel for oil removal and proposed that the potato peel has a good potential as a low cost bio adsorbent for oil removal and to manage environmental pollution